Accessibility of transglutaminase to induce protein crosslinking in gelled food matrices - Influence of network structure. (January 2017) - Grossmann, Lutz; Wefers, Daniel; Bunzel, Mirko; Weiss, Jochen; Zeeb, Benjamin
Abstract: Microbial transglutaminase (mTG) catalyzes the crosslinking of bulk and interfacial proteins, thereby influencing the physical properties of food dispersions. However, little is known about the impact of the spatial distribution of proteins in a gelled matrix on the enzymatic crosslinking. In this study, free and incorporated emulsions were subjected to mTG to induce crosslinking of emulsion interfaces. First, simple caseinate-stabilized emulsions were fabricated by high shear blending (20, 000 rpm, 6 min). Second, emulsion samples were embedded into hydrogel beads using an injection technique. Different alginate (0.5–1.5%) and CaCl2 levels (50–500 mM) were used to modulate the hydrogel pore size and number of junction zones. Third, free and incorporated emulsions were mixed with mTG to investigate the diffusion behavior of the enzyme. Results showed that mTG diffused into the beads to an extent of more than 50%. A delay in ammonia release was observed when emulsions were incorporated into hydrogel beads, whereas protein in free emulsions was instantly crosslinked after mTG was added. These results illustrate that the spatial make-up of biopolymers in gelled matrices play a key role on the enzyme accessibility. Highlights: Alginate, calcium, and oil levels determine the shape and size of hydrogel beads. An immediate crosslinking of adsorbed caseinate was observed in free emulsions. Denser and tighter networks decreased the diffusion and crosslinking rate of mTG.